PENGARUH AUDIT TENURE, KOMPLEKSITAS OPERASI PERUSAHAAN, KUALITAS DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG DENGAN SPESIALISASI INDUSTRI AUDITOR EKSTERNAL SEBAGAI VARIABEL MODERASI - Habibullah Azzuhri; Kamaliah Kamaliah; M. Rasuli (Program Studi Pendidikan Ekonomi Universitas Riau, 2019)
This study aims to examine the effect of audit tenure, the complexity of companyoperations, quality and audit opinion on audit report lag with specialization ofexternal auditor industries as a moderating variable. The samples were determinedby purposive sampling method where 90 manufacturing companies were used assamples. The total sample is 450 companies. The data source used in the study issecondary data. Data analysis for hypothesis testing using Multiple RegressionAnalysis. The results of this study shows that the variable complexity of companyoperations, quality and audit opinion have a significant effect on audit report lag andaudit tenure does not significantly influence audit report lag. The complexity of thecompany's operations and audit opinion has a significant effect on the audit reportlag moderated by the industry of external auditors and there is no influence of audittenure and audit quality on audit report lag which is moderated by the industry'sexternal auditor specialization. Keywords: Audite report lag, tenure audit, complexity of company operations, auditquality, audit opinion and specialization of industrial external auditors.